2020
DOI: 10.1002/iid3.315
|View full text |Cite
|
Sign up to set email alerts
|

Sequential bortezomib and temozolomide treatment promotes immunological responses in glioblastoma patients with positive clinical outcomes: A phase 1B study

Abstract: Background: Glioblastoma (GBM) is an aggressive malignant brain tumor where median survival is approximately 15 months after best available multimodal treatment. Recurrence is inevitable, largely due to O 6 methylguanine DNA methyltransferase (MGMT) that renders the tumors resistant to temozolomide (TMZ). We hypothesized that pretreatment with bortezomib (BTZ) 48 hours prior to TMZ to deplete MGMT levels would be safe and tolerated by patients with recurrent GBM harboring unmethylated MGMT promoter. The second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…Like Ixazomib, Bortezomib (BTZ, Velcade) reversibly blocks the chymotryptic-like activity of the β1 and β5 subunits of the 26S proteasome. BTZ is approved for the treatment of multiple myeloma and mantle cell lymphoma ( Stapnes et al, 2007 ) and has been explored in early phase clinical studies for GBM ( Kubicek et al, 2009 ; Friday et al, 2012 ; Bota et al, 2013 ; Kong et al, 2018 ; Rahman et al, 2020 ). In vitro studies with BTZ alone or in combination with other drugs showed potent anti-cancer activity against various malignancies through multiple mechanisms ( Frankel et al, 2000 ; Nawrocki et al, 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…Like Ixazomib, Bortezomib (BTZ, Velcade) reversibly blocks the chymotryptic-like activity of the β1 and β5 subunits of the 26S proteasome. BTZ is approved for the treatment of multiple myeloma and mantle cell lymphoma ( Stapnes et al, 2007 ) and has been explored in early phase clinical studies for GBM ( Kubicek et al, 2009 ; Friday et al, 2012 ; Bota et al, 2013 ; Kong et al, 2018 ; Rahman et al, 2020 ). In vitro studies with BTZ alone or in combination with other drugs showed potent anti-cancer activity against various malignancies through multiple mechanisms ( Frankel et al, 2000 ; Nawrocki et al, 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…P3 cells were previously generated from the low passage of patient-derived xenografts and were stabilized as a stem-like cell line (characterized by IDH1 wt and MGMT unmethylated promoter [ 15 ]). Patient-derived glioblastoma cells P3 were cultured in neurobasal medium (NBM) supplemented with B-27 serum-free supplement (ThermoFisher Scientific), heparin (100 U/µL), penicillin/streptomycin (1000 U/mL) and basic FGF-2 20 ng/mL, in a 37 °C and 5% CO 2 incubator.…”
Section: Methodsmentioning
confidence: 99%
“…The results suggest that the addition of Bortezomib into the current radiochemotherapy for patients with newly diagnosed GBM was well tolerated, and the PFS and OS rates show more promising values, especially in patients with the MGMT gene promoter methylation [ 97 ]. A more recent report shows that a well-tolerated sequential treatment using Bortezomib plus TMZ promotes Th1-driven immunological responses in a group of patients showing better clinical outcomes [ 98 ].…”
Section: Novel Therapeutic Strategies For Gbmmentioning
confidence: 99%